Toward Theology of Science: Philosophical Reflection On The Development Of Religion-Based Science - Muslih, Mohammad (KALAM, 2019)
The relationship between science and religion is one of the issues that has not been resolved completely until now. Although some universities in Indonesia and even Malaysia have developed academic traditions with the paradigm of integration of science, they still leave a fundamental problem related to aspects of scientific science developed with religion. To meet scientific and objective criteria, science must avoid the element of subjectivity of scientists, and eliminate the intersubjectivity of tradition and culture. This paper will analyze, especially to emphasize the position of philosophy in the development of religion-based science, as well as reflection for the development of philosophical sciences. This paper will discuss two main problems, the investigation of the religious dimension for science, and the role of religion-based science development for the development of philosophical sciences. The study found that in addition to the theoretical framework and scientific paradigm, there is one more thing that cannot be left behind in the process of developing science, namely the theological assumptions or theological dimensions of science. So that the basis of the development of science not only consists of theories and paradigms, but also theological assumptions. This article concludes that the theological dimension allows for the development of religion-based science.